GAYA HIDUP MINUM KOPI DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN KOPI (STUDI KASUS PADA KOPI KENANGAN GANDARIA CITY - JAKARTA) - Selvi, Selvi; Ningrum, Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Coffee is a drink that is preferred among the people. Coffee is a type of beverage that comes from the processing and extraction of coffee beans. Coffee comes from Arabic qahwah which means strength. Coffee can be said as a drink that provides energy. At this time there was a booming coffee shop business. These days the emergence of various types of coffee shops that sell various types of coffee drinks are supported by the interior and various unique concepts that can not be separated from people’s lives. This has led to consumptive behavior that mainly occurs among young people so they are happy to be in a coffee shop. This study aims to explain and find out whether there is an influence of lifestyle on a person’s purchasing decisions in the Coffee Memories of Gandaria City, especially among young people. The independent variables used in this study are Activity, Interest and Opinion. Sample population used in this study are visitors or consumers who are or have made purchases of Kengangan Gandaria City Coffee as many as 100 people. This research uses descriptive method. Based on the results of the determination test shows the number of 0.700 so it can be concluded that purchasing decisions are significantly influenced by lifestyle. This shows that the occurrence of consumptive lifestyles that affect a person in making purchase decisions. Lifestyle variables on opinion indicators provide the most powerful influence compared to other indicators. Keywords: lifestyle, buyer decision, coffe shop, food and beverage product